An MRI-compatible loading device to assess knee joint cartilage deformation: Effect of preloading and inter-test repeatability. Issue 12 (18th September 2015) - Wang, Hongsheng; Koff, Matthew F.; Potter, Hollis G.; Warren, Russell F.; Rodeo, Scott A.; Maher, Suzanne A.
Abstract: It has been suggested that the extent and location of cartilage deformation within a joint under compressive loading may be predictive of predisposition to further degeneration. To explore this relationship in detail requires the quantification of cartilage deformation under controlled loads on a per-patient basis in a longitudinal manner. Our objectives were (1) to design a device capable of applying controllable axial loads while ensuring repeatable within-patient tibiofemoral positioning during magnetic resonance imaging (MRI) scans and (2) to determine the duration for which load should be maintained prior to the image acquisition, for a reproducible measurement of cartilage deformation, within the restraints of a clinical setting. A displacement control loading device was manufactured from MRI-compatible materials and tested on four volunteers for the following five scans: an unloaded scan, two repeat immediate scans which were started immediately after the application of 50% body weight, and two repeat delayed scans started 12 min after load application. Outcome measures included within-patient changes in tibiofemoral position and cartilage deformation between repeat loaded scans. The differences in tibiofemoral position between repeat loaded scans were <1 mm in translation and <2° in rotation. Cartilage deformations were more consistent in the delayed scans compared to the immediate scans. We conclude that our loading device can ensure repeatable tibiofemoral positioning to allow for longitudinal studies, and the delayed scan may enable us to obtain more reproducible measurements of cartilage deformation in a clinical setting.